2021
DOI: 10.1159/000517148
|View full text |Cite
|
Sign up to set email alerts
|

The Difficulties Encountered by Pediatric Cochlear Implant Patients and Their Parents during the COVID-19 Pandemic

Abstract: <b><i>Introduction:</i></b> The daily escalation in incidence and mortality caused by Coronavirus disease (COVID-19) has mandated forced curfew in our country (same as many other countries) to limit the spread of infection. This is predicted to have a more negative impact on cochlear implant (CI) patients since this group of patients needs a unique type of psychological, medical, and technical care in addition to a daily rehabilitation program. <b><i>Methods:</i></b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…By contrast with older adults, pediatric patients experienced little disruption in access to CIs during the pandemic, despite the many barriers facing this population during this period (4,5). Given the widespread appreciation for critical periods of neuroplasticity during pediatric development and resultant importance of early implantation, many CI centers rendered cochlear implantation for congenital deafness of "urgent" necessity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast with older adults, pediatric patients experienced little disruption in access to CIs during the pandemic, despite the many barriers facing this population during this period (4,5). Given the widespread appreciation for critical periods of neuroplasticity during pediatric development and resultant importance of early implantation, many CI centers rendered cochlear implantation for congenital deafness of "urgent" necessity.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic introduced multiple barriers to cochlear implantation (1)(2)(3)(4)(5), and thus far, the magnitude of the pandemic's effect on cochlear implant (CI) hearing healthcare in the United States is unknown. One of the primary challenges to understanding the extent of the pandemic's national effect on cochlear implantation extends from the pragmatic limitation in the United States surrounding the absence of a national healthcare registry.…”
Section: Introductionmentioning
confidence: 99%
“…One study involving children with cochlear implants in the United Arab Emirates throughout the COVID‐19 pandemic revealed that timely access to cochlear mapping appointments was delayed for these children, with most parents lacking access to adequate follow‐up (Ayas et al, 2020 ). Another study conducted in Saudi Arabia by Telmesani et al ( 2021 ) following paediatric cochlear implant patients during COVID‐19 similarly reported difficulties for patients in obtaining follow‐up cochlear programming appointments, with access to surgery, audiology and speech and language pathology delayed especially during lockdown periods. These findings highlight the worldwide impact of COVID‐19 on healthcare service delivery.…”
Section: Discussionmentioning
confidence: 99%
“…As the access to primary health care decreased due to restrictions, telehealth services began to be needed (Wong, Ming, Maslow, & Gifford, 2020). All health systems, hospitals, and clinics started to implement telehealth services rapidly, and thus patient care and treatment services changed (Telmesani, Said, Mahrous, & Alrusayyis, 2021). As in most health fields, the audiology unit has also been negatively affected by the traditional face-to-face appointment system.…”
Section: Discussionmentioning
confidence: 99%